Effects of Dietary Supplementation of a Resin-Purified Aqueous-Isopropanol Olive Leaf Extract on Meat and Liver Antioxidant Parameters in Broilers - Konstantina Vasilopoulou; Georgios A. Papadopoulos; Styliani Lioliopoulou; Ioanna Pyrka; Nikolaos Nenadis; Soumela Savvidou; George Symeon; Vassilios Dotas; Ioannis Panitsidis; Georgios Arsenos; Ilias Giannenas (MDPI AG, 2023)
Olive leaves are byproducts οf the agro-industrial sector and are rich in bioactive compounds with antioxidant properties. They could be supplemented in poultry diets powdered or less frequently as extracts to improve performance, health and product quality. The objective of this study was to investigate the possible beneficial effects of an aqueous isopropanol olive leaf extract-purified through filtration (250-25 µm) and a resin (XAD-4)-when supplemented in broiler chickens' diets, on meat quality parameters, focusing mainly on antioxidant parameters as there is limited published information. For this purpose, four-hundred-and-eighty-day-old broilers were randomly assigned to four dietary treatments: T1 (control: basal diet); T2 (1% olive leaf extract); T3 (2.5% olive leaf extract); T4 (positive control: 0.1% encapsulated oregano oil commercially used as feed additive). At the end of the experimental period (day 42), the birds were slaughtered, and samples from breast, thigh meat and liver were collected for antioxidant parameters evaluation. On day 1, after slaughter, in thigh meat, Malondialdehyde (MDA) was lower in T2 compared to T3, and total phenolic content (TPC) was higher in T2 compared to T3 and T4. Total antioxidant capacity (TAC) was increased in T2 and T4 breast meat compared to the control. In liver, T4 treatment resulted in higher TPC. The lack of dose-dependent effect for olive leaf extract may be attributed to the pro-oxidant effects of some bioactive compounds found in olive leaves, such as oleuropein, when supplemented at higher levels. In summary, it can be inferred that the inclusion of 1% olive leaf extract in the feed of broilers has the potential to mitigate oxidation in broiler meat and maybe enhance its quality.